Investment attractiveness of thermoelectric power sources using low-grade energy of the environment - Mykytiuk, P.D.; Mykytiuk, O.Yu. (Journal of Thermoelectricity, 2024)
The article shows the possibilities of obtaining economic advantages when using a thermoelectric method of converting low-grade energy, which is reliable, autonomous and provides for the use of power sources with a long service life, using the environmental energy to provide power to low-power devices located in remote and hard-to-reach places. Bibl. 4, Figs. 1, Table. 1.